2022
DOI: 10.1186/s13031-022-00443-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the mental health of Rohingya refugees with pre-existing health problems in Bangladesh

Abstract: Background Mental disorders among refugees have been well explored in several studies. However, longitudinal studies on the impact of the pandemic on refugee populations are widely lacking. This study was designed to examine the impact of the current pandemic on the mental health of Rohingya refugees living in Bangladesh. Method This longitudinal study involved a convenience sample of 732 Rohingya people with pre-existing health problems who lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Refugee communities worldwide experienced stressors similar to those experienced by refugees in Gaza, such as increased GBV, nancial strain, food insecurity, and poor access to education and were all found to exert a negative impact on mental health during the pandemic (35)(36)(37)(38). Protective measures, such as physical distancing, were found to be very challenging, if not impossible, for refugees living in different encampments across the world (39).…”
Section: Discussionmentioning
confidence: 99%
“…Refugee communities worldwide experienced stressors similar to those experienced by refugees in Gaza, such as increased GBV, nancial strain, food insecurity, and poor access to education and were all found to exert a negative impact on mental health during the pandemic (35)(36)(37)(38). Protective measures, such as physical distancing, were found to be very challenging, if not impossible, for refugees living in different encampments across the world (39).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tarannum et al, 2019 reported the findings from an intervention study. The remaining were qualitative study (n = 3) (Zaman et al, no date;Wells et al, 2019;Welton-Mitchell et al, 2019), mixed method study (n = 2) (Shaw et al, 2019;Christensen, Ahsan and Mandal, 2020), longitudinal study (n = 2) (O'connor and Seager, 2021;Palit et al, 2022) design.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies (n = 16) were conducted in Bangladesh (Zaman et al, no date;Riley et al, 2017Tarannum et al, 2019;Wells et al, 2019;Mahmuda et al, 2019;Christensen, Ahsan and Mandal, 2020;Hossain et al, 2020Tay et al, 2021;Haque, 2021b, 2021a;O'connor and Seager, 2021;Awang, Mohamad and Maria Awaluddin, 2022;Palit et al, 2022), for example, Wells et al, 2019 conducted a qualitative study on Rohingya refugees, living in the camps, whereas some studies (n = 8) were conducted in Malaysia (A. K. Tay et al, 2019;Alvin Kuowei Tay et al, 2019;Shaw et al, 2019;Welton-Mitchell et al, 2019;Kaur et al, 2020;Tay, Khat Mung, et al, 2020;Tay et al, 2022), such as a cross sectional study by Tay et al, 2019.…”
Section: Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…10 This includes mental health, for which problems have been exacerbated in displaced populations due to the COVID-19 pandemic. 11 There is often a limit to the global attention span, as we see headlines discussed one week and overlooked a few weeks later. As with COVID-19 diverting resources within a population, a new global crisis can divert resources among populations.…”
mentioning
confidence: 99%